Aplikasi Pencarian Donor Darah Menggunakan Metode Personal Extreme Programming Berbasis Android - Muhammad Fajri Riki; Irman Effendy (LPPM UBHINUS MALANG, 2022)
In 2019, the world was shocked by the COVID-19 outbreak. COVID-19 causes a reduction in blood stocks and donors for fear of being exposed to COVID-19 when donating. The search for blood donors by patients tends to be difficult because it is difficult to find donors. There are still many patients who have difficulty getting blood donors because the blood stock needed is not always available. Many patients use social media to find blood donors but it is less effective, donor information is unclear, and not always on target. Based on these problems, the solution is to create an android-based application as a platform that can help search for blood donors and connect patients and donors. This app is built with Flutter, Firebase and Google Cloud frameworks. The method used in the development of this application is Personal Extreme Programming (PXP) with Black Box testing, the results are that the application is made to work properly as it functions. The results of this study are an android-based blood donor finder application that can make it easier to find donors.